2019
DOI: 10.1084/jem.20182325
|View full text |Cite
|
Sign up to set email alerts
|

Core 1–derived mucin-type O-glycosylation protects against spontaneous gastritis and gastric cancer

Abstract: Core 1–derived mucin-type O-glycans (O-glycans) are a major component of gastric mucus with an unclear role. To address this, we generated mice lacking gastric epithelial O-glycans (GEC C1galt1−/−). GEC C1galt1−/− mice exhibited spontaneous gastritis that progressed to adenocarcinoma with ∼80% penetrance by 1 yr. GEC C1galt1−/− gastric epithelium exhibited defective expression of a major mucus forming O-glycoprotein Muc5AC relative to WT controls, which was associated with impaired gastric acid homeostasis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 61 publications
4
41
0
Order By: Relevance
“…Overexpression of Tn antigen has been shown to promote tumor growth in CRC (11,51) and pancreatic cancer (13). Moreover, in some models the mere abrogation of T-synthase/COSMC is sufficient to induce oncogenic features and to augment tumorigenesis of otherwise healthy cells (12,52). In contrast, enhanced T antigen expression also correlates to bad prognosis and oncogenesis in, for instance, breast (31,53,54) and head and neck cancer (55).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Tn antigen has been shown to promote tumor growth in CRC (11,51) and pancreatic cancer (13). Moreover, in some models the mere abrogation of T-synthase/COSMC is sufficient to induce oncogenic features and to augment tumorigenesis of otherwise healthy cells (12,52). In contrast, enhanced T antigen expression also correlates to bad prognosis and oncogenesis in, for instance, breast (31,53,54) and head and neck cancer (55).…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown the critical roles of mucins in tumorigenesis (van Putten and Strijbis, 2017;Maeda et al, 2018;Ganguly et al, 2020;Liu et al, 2020), which indicated their prospective usefulness in cancer diagnosis, prognosis, and therapy (Nabavinia et al, 2017;Aithal et al, 2018;Guo et al, 2018;Lucchetta et al, 2019;Pothuraju et al, 2020). Previous studies have raised hope that MUC4 can be a good candidate marker for pancreatic malignancy (Trabbic et al, 2019;Gautam et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…C1GALT1 has been shown to be a tumor suppressor gene in pancreatic cancer since the absence of C1GALT1 expression promotes the development and metastasis of pancreatic cancer ( 30 ). However, in another study, C1GALT1 served a different role ( 31 ). Liu et al ( 31 ) found that in C1GALT1 -knockout mice, spontaneous gastroenteritis and consequently gastric antral adenocarcinoma were improved in the gastric mucosal epithelial cells, which indicates that C1GALT1 -mediated O -glycosylation is very important for gastric mucosal and gastric homeostasis protection ( 31 ).…”
Section: Introductionmentioning
confidence: 96%
“…However, in another study, C1GALT1 served a different role ( 31 ). Liu et al ( 31 ) found that in C1GALT1 -knockout mice, spontaneous gastroenteritis and consequently gastric antral adenocarcinoma were improved in the gastric mucosal epithelial cells, which indicates that C1GALT1 -mediated O -glycosylation is very important for gastric mucosal and gastric homeostasis protection ( 31 ). However, the use of samples from different sources or at different tumor stages may have contributed to the observed dual function of C1GALT1 ; hence, the true role of the gene remains elusive.…”
Section: Introductionmentioning
confidence: 96%